Efficacy of copper sulfate and potassium permanganate in reducing bacterial infection and mortality in polycultured farmed fish at El Menoufia, Egypt: A microbiological and environmental analysis - Mosleh, Amani; El-Bialy, Amani; El-Zahaby, Dina; El-Saadany, Amr; Anter, Alaa; khalefa, Hanan (Iraqi journal of veterinary sciences, 2026)
Managing fish health effectively requires understanding bacterial coinfections and environmental factors.The effects of copper sulfate and potassium permanganate on bacterial infection in naturally infected farmed fish obtained from private fish farms in Wadi El-Natrun, El Menoufia, Egypt, with high mortality rates have been evaluated. Forty Mugil capito and seventy-four Oreochromis niloticus were randomly selected from these farms. One pure isolate, including E. coli (n=11), Enterobacter spp. (n=5), Klebsiella spp. (n=5), Salmonella spp. (n=3), Pseudomonas spp. (n=12), Aeromonas spp. (n=2), and Enterococcus spp. (n=13), was recovered from the fish samples. Enterococcus spp., E. coli, and Pseudomonas were predominant in both fish species. Compared with other farms, Farms 4 and 5 presented higher frequencies of Pseudomonas spp., Enterobacteriaceae, and E. coli infections in clinically affected fish (χ2 = 6.02, p = 0.031). Significant differences were observed between farms (χ2 = 9.37, p = 0.024). These isolates were further identified via 16S rRNA gene sequencing and phylogenetic analysis. A water analysis revealed that the phosphate, sulfate, hardness, and chloride levels were above permissible limits on farms 4 and 5. During this study, copper sulfate (CuSO4) and potassium permanganate (KMnO4) were applied at 24-hour intervals for seven days, and their effects on bacterial loads, coliform counts, and mortality in morbid Nile tilapia were examined. The pretreatment samples served as a control group. CuSO4 and KMnO4 effectively reduced the bacterial load and mortality rates. Compared with untreated fish, those treated with CuSO4 or KMnO4 had survival rates of 80.0% and 70.2%, respectively.